1999
DOI: 10.2527/1999.77suppl_2213x
|View full text |Cite
|
Sign up to set email alerts
|

The Beltsville sperm sexing technology: high-speed sperm sorting gives improved sperm output for in vitro fertilization and AI

Abstract: The Beltsville sperm sexing technology is currently the only effective means of altering the sex ratio of offspring in livestock. The method is based on the flow-cytometric separation of X- and Y-chromosome-bearing sperm based on X/Y DNA content difference. It is an effective means of producing progeny of predetermined sex in cattle, swine, sheep, and laboratory animals. The method involves treating sperm with a DNA-binding fluorochrome, Hoechst 33342, and flow-cytometrically sorting them into separate X and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 23 publications
(29 reference statements)
0
53
0
Order By: Relevance
“…The tip of the flow cell was remolded to provide 2-3 times the orientation capability of the needle system. This novel nozzle resulted in a greater orienting percentage [35]. Rens et al [45] a n d J o h n s o n e t a l .…”
Section: Flow Cytometer Modification and X-and Y-sperm Separationmentioning
confidence: 99%
See 3 more Smart Citations
“…The tip of the flow cell was remolded to provide 2-3 times the orientation capability of the needle system. This novel nozzle resulted in a greater orienting percentage [35]. Rens et al [45] a n d J o h n s o n e t a l .…”
Section: Flow Cytometer Modification and X-and Y-sperm Separationmentioning
confidence: 99%
“…Application of these paint to a FISH protocol for bull sperm resulted in clear identification of more than 90% of sperm. When the fluorescence-labeled X-and Y-specific paints were tested in samples of bull sperm sorted using the Beltsville sperm sexing technology [35], the results indicated that the FISH procedure is robust, reproducible, and simple with high efficiency for evaluation of the sex of sorted sperm [53].…”
Section: E C O N D E N S a T I O N ; T H I S P R O V I D E S A S E T mentioning
confidence: 99%
See 2 more Smart Citations
“…Sexing of semen and of embryos provides in species and production circumstances where one sex is preferred, a way to produce the wanted type of animal (Betteridge et al, 1981;Johnson et al, 1998). Sexing of embryos is a technique that is rather reliable nowadays and currently used on a rather large extent.…”
Section: Sexingmentioning
confidence: 99%